The Novel Secreted Factor MIG-18 Acts with MIG-17/ADAMTS to Control Cell Migration in Caenorhabditis elegans. Issue 2 (1st February 2014) - Kim, Hon-Song; Kitano, Yuko; Mori, Masataka; Takano, Tomomi; Harbaugh, Thomas Edward; Mizutani, Kae; Yanagimoto, Haruka; Miwa, Sayaka; Ihara, Shinji; Kubota, Yukihiko; Shibata, Yukimasa; Ikenishi, Kohji; et al.
Abstract: The migration of Caenorhabditis elegans gonadal distal tip cells (DTCs) offers an excellent model to study the migration of epithelial tubes in organogenesis. mig-18 mutants cause meandering or wandering migration of DTCs during gonad formation, which is very similar to that observed in animals with mutations in mig-17, which encodes a secreted metalloprotease of the ADAMTS (a d isintegrin a nd m etalloprotease with t hrombos pondin motifs) family. MIG-18 is a novel secreted protein that is conserved only among nematode species. The mig-17 (null) and mig-18 double mutants exhibited phenotypes similar to those in mig-17 (null) single mutants. In addition, the mutations in fbl-1 /fibulin-1 and let-2 /collagen IV that suppress mig-17 mutations also suppressed the mig-18 mutation, suggesting that mig-18 and mig-17 function in a common genetic pathway. The Venus-MIG-18 fusion protein was secreted from muscle cells and localized to the gonadal basement membrane, a tissue distribution reminiscent of that observed for MIG-17 . Overexpression of MIG-18 in mig-17 mutants and vice versa partially rescued the relevant DTC migration defects, suggesting that MIG-18 and MIG-17 act cooperatively rather than sequentially. We propose that MIG-18 may be a cofactor of MIG-17 /ADAMTS that functions in the regulation of the gonadal basement membrane to achieve proper direction of DTC migration during gonadogenesis.